2022
DOI: 10.1055/a-1594-1515
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of cystic duct stones and Mirizzi’s syndrome: experience at an academic medical center

Abstract: Background and study aims Cystic duct stones (CDS) are challenging to treat with conventional ERCP techniques due to the small diameter and tortuous nature of the cystic duct. There have been limited studies focused on endoscopic management of CDS. We present our experience managing CDS endoscopically and demonstrate that new advances in endoscopic technology have rendered CDS easier to manage. Patients and methods From 2013 to 2020, we prospectively maintained a database of patients undergoing endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We could achieve clearance of all cystic duct stones along with the CBD stones. In a recent study by Pawa et al, 11 cholangioscopy with EHL was performed in 18 procedures to achieve cystic duct stone clearance. Cystic duct stone clearance was achieved in all patients and our findings are similar to the study.…”
Section: Discussionmentioning
confidence: 99%
“…We could achieve clearance of all cystic duct stones along with the CBD stones. In a recent study by Pawa et al, 11 cholangioscopy with EHL was performed in 18 procedures to achieve cystic duct stone clearance. Cystic duct stone clearance was achieved in all patients and our findings are similar to the study.…”
Section: Discussionmentioning
confidence: 99%
“…ERCP with cholangioscopy allows for fragmentation and extraction of cystic duct or bile duct stones in patients with Mirizzi syndrome. This approach is predominantly described in Mirizzi syndrome with no fistula to allow for intubation of the cystic duct and clearance of stones 11 . A recent literature review identified 8 prior reports of cholangioscopic management of Mirizzi syndrome with a cholecystobiliary fistula 12–15 …”
Section: Figmentioning
confidence: 99%
“…This approach is predominantly described in Mirizzi syndrome with no fistula to allow for intubation of the cystic duct and clearance of stones. 11 A recent literature review identified 8 prior reports of cholangioscopic management of Mirizzi syndrome with a cholecystobiliary fistula. [12][13][14][15] In the majority of cases this approach was successful using either holmium laser or EHL for stone fragmentation.…”
mentioning
confidence: 99%
“…Traditionally, surgery has been performed for PCS because endoscopic treatment is challenging 2 . Peroral cholangioscopy (POCS) and electrohydraulic lithotripsy (EHL) are now available for biliary stones, including cystic duct stones, which are difficult to treat with conventional procedures 3 4 5 . Here, we report a case of endoscopic removal of a cystic duct remnant stone using POCS, EHL, and steps targeted at its efficient removal.…”
Section: Figmentioning
confidence: 99%